Thermo-Economic Comparison Between Organic Rankine Cycle and Binary-Flashing Cycle for Geothermal Energy - Zhao, Yuan; Du, Bowen; Chen, Shunyi; Zhao, Jun; Gong, Yulie; Bu, Xianbiao; Li, Huashan; Wang, Lingbao (Frontiers in Earth Science, 2021)
Geothermal energy is a characteristic of widely distributed, high capacity factor, high reliability, and lower environmental impact potential values. And it will play an important role in achieving the goal of carbon neutral carbon peak. Nonetheless, geothermal energy presents its own particular challenges, i.e., the high investment cost and long payback period. The binary flashing cycle (BFC) system is proved to be a promising power generation technology due to the efficient and full utilization of a low-grade heat source. While the economic performance still needs further evaluation, in the present study, the thermo-economic comparison between organic Rankine cycle (ORC) and the BFC for geothermal energy has been investigated. R245fa has been chosen as the working fluid. Considering the thermodynamic and economic performance simutaneously, several evaluation indicators were selected including thermal efficiency, exergy efficiency, net power output per ton geothermal water, heat exchanger area, and heat recovery efficiency, and the system modeling and comparison were presented. The simulation results reveal that the BFC system obtains 32% more net power output than the ORC system under the working conditions investigated. The heat recovery efficiency of the BFC is 1.96 times as much as that of the ORC, which indicates that the BFC can realize the full utilization of low-grade energy. And more heat exchanger areas are required in the BFC system. What is more, the preliminary discussion of the economic feasibility of BFC system applied in the FengShun geothermal power plant is presented. The payback period of the BFC is just 6.0 years under the generation pressure of 600 kPa. It is indicated that the BFC system has obvious economic benefits, especially in a nonflowing geothermal well.